KETERBUKAAN BERMAZHAB DALAM REALITI DI MALAYSIA: KEPERLUAN ATAU KECELARUAN? Openness in Practising Madhhabs in Malaysian Reality: A Necessity or Ambiguity? - Ahmad Farid, Inarah; Man, Saadan (Jurnal Syariah, 2012)
Malay Muslims are regarded as loyal adherents of Shafi‘i madhhab since they embraced Islam centuries ago. The strict adherence to the madhhab, however, sometimes leads them to some difficulties when some Shafi‘i standpoints do not suit certain circumstances or needs. Hence, they start to look for viewpoints from other madhhabs, which are considered as more adaptable to their situation and need. However, this step is considered as a last resort when no acceptable answer is found in the madhhab. This move should also be differentiated from the idea of borderless fiqh propounded by the reformists to free the Malays from holding to a specific madhhab. Whilst occasionally adopting the views of other madhhabs is permissible by the majority of Malay ulamas, being free from holding to a certain madhhab is seen as tantamount to heresy, and, therefore, should not be allowed. There is a thin line between both situations and this could lead one to confusion if it is not properly understood. This paper attempts to analyse the issues based on the perspectives of the Islamic traditionalism and reformism. Although the conflicting thoughts of both parties on this particular issue are hard to reconcile, there are some common standpoints that can lead to positive collaboration between them.